Optimization and Identification of Antioxidant Peptide from Underutilized Dunaliella salina Protein: Extraction, In Vitro Gastrointestinal Digestion, and Fractionation. (20th August 2019) - Xia, Enqin; Zhai, Lu; Huang, Zhigang; Liang, Hairong; Yang, Hui; Song, Gang; Li, Weiqiao; Tang, Huanwen
Abstract : DPPH scavenging peptides (<3kDa) from underutilized Dunaliella salina protein were obtained by the following successive treatment, i.e., ultrasound extraction, simulated in vitro gastrointestinal digestion hydrolyzation, and membrane ultrafiltration classification. The optimal condition for ultrasound-assisted extraction was an ultrasound wave with 800 W of power treating a mixture of 60 mL of 1.0 mol L −1 NaOH and 2 g algae powder for 15 min. A high correlation (r=0.8146) between DPPH scavenging activity and yield of the intact peptides showed their antioxidant capacity. Simulated in vitro digestion assay resulted in excellent DPPH scavenging activity of the total peptide, amounting to (86.5 ± 10.1)%, comparing with the nondigestion samples at (46.8 ± 6.5)%. After fractionation, the 500-1000 Da fraction exhibited the highest DPPH scavenging activity (81.2 ± 4.0)%, increasing 1.5 times due to digestion. Then, the 500-1000 Da fraction was analyzed by RPLC-Q Exactive HF mass spectrometer, and 4 novel peptides, i.e., Ile-Leu-Thr-Lys-Ala-Ala-Ile-Glu-Gly-Lys, Ile-Ile-Tyr-Phe-Gln-Gly-Lys, Asn-Asp-Pro-Ser-Thr-Val-Lys, and Thr-Val-Arg-Pro-Pro-Gln-Arg, were identified. From these amino acid sequences, hydrophobic residues accounted for 56%, which indicated their high antioxidant property. The results indicated that underutilized protein of Dunaliella salina could be a potential source of antioxidative peptides through simulated in vitro gastrointestinal digestion.